Did I do this right?

  • Thread starter AKG
  • Start date
  • #1
AKG
Science Advisor
Homework Helper
2,565
4
I posted these a while back, I just wanted to be certain I did it right before I hand it in:

---------------------------------

Question 1

Suppose that h : [itex]\mathbb{R} \to \mathbb{R}[/itex] is continuous. Calculate f', if f : [itex]\mathbb{R}^2 \to \mathbb{R}[/itex] is the function:

[tex]f(x, y) = \int _{\sin (xy)} ^{\cos (xy)} h(t)dt[/tex]


Question 2

Let

[tex]f(x,y)=\left\{\begin{array}{cc}\frac{x^4 + y^4}{x^2 + y^2},&\mbox{ if }
(x,y)\neq (0,0)\\0, & \mbox{ if } (x,y) = (0,0)\end{array}\right[/tex]

Show that f is differentiable at (0,0)

---------------------------------

Question 1

[tex]f' = \left [D_1f(x, y) \ \ \ \ D_2f(x, y)\right ][/tex]

[tex]f' = \left [\frac{\partial}{\partial x}\int_{\sin (xy)} ^{\cos (xy)} h(t)dt \ \ \ \ \frac{\partial}{\partial y}\int_{\sin (xy)} ^{\cos (xy)} h(t)dt\right ][/tex]

Let H be the antiderivative of h (which exists because h is continuous), then:

[tex]f' = \left [\frac{\partial}{\partial x}\left ( H(\cos xy) - H(\sin xy) \right ) \ \ \ \ \frac{\partial}{\partial y}\left ( H(\cos xy) - H(\sin xy)\right ) \right ][/tex]

[tex]f' = -\left [y(\sin (xy)h(\cos (xy)) + \cos (xy)h(\sin (xy))) \ \ \ \ x(\sin (xy)h(\cos (xy)) + \cos (xy)h(\sin (xy)))\right ][/tex]


Question 2

Proposition: f is differentiable at (0, 0), and the derivative at that point is the zero transformation.

Proof:

It suffices to show that:

[tex]L = 0[/tex]

Where [itex]h = (h_1, h_2) \in \mathbb{R}^2[/itex], and:

[tex]L = \lim _{h \rightarrow 0} \frac{|f(h)|}{|h|}[/tex]

If [itex]h_1 = 0[/itex] and [itex]h_2 \neq 0[/itex], then:

[tex]L = \lim _{h \rightarrow 0} \frac{h_2^4}{|h_2^3|} = \lim _{h \rightarrow 0} |h_2| = 0[/tex]

Clearly, if [itex]h_1 \neq 0[/itex] and [itex]h_2 = 0[/itex], then we also have that L = 0. Now, if neither component of h is zero, then:

[tex]L = \lim _{h \rightarrow 0} \frac{|h_1^4 + h_2^4|}{(h_1^2 + h_2^2)^{3/2}}[/tex]

[tex]L = \lim _{h \rightarrow 0} \frac{|(h_1^2 + h_2^2)^2 - 2h_1^2h_2^2|}{(h_1^2 + h_2^2)^{3/2}}[/tex]

[tex]L = \lim _{h \rightarrow 0} \left ||h| - \frac{2h_1^2h_2^2}{(h_1^2 + h_2^2)^{3/2}} \right |[/tex]

[tex]L = 2\lim _{h \rightarrow 0} \frac{h_1^2h_2^2}{(h_1^2 + h_2^2)^{3/2}}[/tex]

[tex]L = 2\lim _{h \rightarrow 0} |h| \left (\frac{h_1h_2}{h_1^2 + h_2^2} \right )^2[/tex]

Now, consider the function [itex]g(z) = z + z^{-1}[/itex] for positive [itex]z \in \mathbb{R}[/itex]. Simple analysis shows that g reaches a minimum at 2, so:

[tex]z + \frac{1}{z} \geq 2[/tex]

Now, let [itex]|h_1||h_2|^{-1} = z[/itex]:

[tex]\frac{|h_1|}{|h_2|} + \frac{|h_2|}{|h_1|} \geq 2[/tex]

[tex]h_1^2 + h_2^2 \geq 2|h_1||h_2|[/tex]

[tex]\frac{1}{2} \geq \frac{|h_1||h_2|}{h_1^2 + h_2^2}[/tex]

[tex]\frac{1}{4} \geq \left ( \frac{h_1h_2}{h_1^2 + h_2^2} \right )^2[/tex]

[tex]2|h|\frac{1}{4} \geq 2|h|\left ( \frac{h_1h_2}{h_1^2 + h_2^2} \right )^2[/tex]

So:

[tex]L \leq \frac{1}{2}\lim _{h \rightarrow 0} |h| = 0[/tex]

Clearly, |f(h)| and |h| are non-negative, so:

[tex]0 \leq \lim _{h \rightarrow 0} \frac{|f(h)|}{|h|} = L \leq 0[/itex]

This proves that f is indeed differentiable at (0, 0), and 0 (the zero transformation) is its derivative there. Q.E.D.
 

Answers and Replies

Related Threads on Did I do this right?

  • Last Post
Replies
15
Views
2K
  • Last Post
Replies
2
Views
1K
  • Last Post
Replies
1
Views
4K
  • Last Post
Replies
9
Views
1K
  • Last Post
Replies
1
Views
1K
  • Last Post
Replies
1
Views
869
  • Last Post
Replies
2
Views
1K
  • Last Post
Replies
11
Views
3K
  • Last Post
Replies
2
Views
2K
Replies
1
Views
4K
Top